Extent, causes and rates of upland soil erosion in England and Wales - McHugh, Marianne (Cranfield University, 2000)
The uplands of England and Wales are internationally important for nature conservation and are prized nationally for their landscape, recreational and cultural value. Reflecting this status, recent appeals, have prompted fundamental research into degradation of the upland habitat. This work was instigated as part of that research to determine the current extent, causes and rates of upland degraded soil. The research was based principally upon a statistically robust and objective selection of 399 field sites. Erosion extent and condition were recorded and related to morphology, environment and management conditions within both field sites and sub-catchments. The short-term rate of soil loss was determined through the completion of cross-sectional traverses on erosion gullies in 1997 and in 1999. Longer-term variations in the extent and causes of upland erosion were established through the interpretation of aerial photographs taken between 1946 and 1989. Erosion measured on field sites in 1999 was estimated to represent 24 566 ha and 0.284 km3 in upland England and Wales. Of this, 18 025 ha and 0.242 km3was attributed to water erosion, which included large-scale blanket peat degradation. Biotic factors accounted for 6 541 ha and 0.041 km3 of erosion, evident on 68% of eroded field sites. Wind was a negligible contributor to upland erosion. Upland eroded area in England and Wales increased by over 518 ha between 1997 and 1999: humans and animals were responsible for 99.9% of this increase. Within the last half-century, the creation and perpetuation of erosion was also principally due to humans and animals. Water-eroded features on both peat and mineral soils showed stabilisation and revegetation throughout the same period. These results expose the highly degraded state of the upland environment and the alarming rate at which erosion is proceeding. The implications of this erosion and proposals for mitigation policies are discussed.